LEF1‐mediated MMP13 gene expression is repressed by SIRT1 in human chondrocytes. Issue 7 (7th April 2017) - Elayyan, Jinan; Lee, Eun‐Jin; Gabay, Odile; Smith, Christopher A.; Qiq, Omar; Reich, Eli; Mobasheri, Ali; Henrotin, Yves; Kimber, Susan J.; Dvir‐Ginzberg, Mona
ABSTRACT: Reduced SIRT1 activity and levels during osteoarthritis (OA) promote gradual loss of cartilage. Loss of cartilage matrix is accompanied by an increase in matrix metalloproteinase (MMP) 13, partially because of enhanced LEF1 transcriptional activity. In this study, we assessed the role of SIRT1 in LEF1‐mediated MMP13 gene expression in human OA chondrocytes. Results showed that MMP13 protein levels and enzymatic activity decreased significantly during SIRT1 overexpression or activation by resveratrol. Conversely, MMP13 gene expression was reduced in chondrocytes transfected with SIRT1 siRNA or treated with nicotinamide (NAM), a sirtuin inhibitor. Chondrocytes challenged with IL‐1β, a cytokine involved in OA pathogenesis, enhanced LEF1 protein levels and gene expression, resulting in increased MMP13 gene expression; however, overexpression of SIRT1 during IL‐1β challenge impeded LEF1 levels and MMP13 gene expression. Previous reports showed that LEF1 binds to the MMP13 promoter and transactivates its expression, but we observed that SIRT1 repressed LEF1 protein and mRNA expression, ultimately reducing LEF1 transcriptional activity, as judged by luciferase assay. Finally, mouse articular cartilage from Sirt1 ‒ /‒presented increased LEF1 and MMP13 protein levels, similar to human OA cartilage. Thus, demonstrating for the first time that SIRT1 represses MMP13 in human OA chondrocytes, which appears to be mediated, at least in part, through repression of the transcription factor LEF1, a known modulator of MMP13 gene expression.—Elayyan, J., Lee, E.‐J., Gabay, O., Smith, C. A., Qiq, O., Reich, E., Mobasheri, A., Henrotin, Y., Kimber, S. J., Dvir‐Ginzberg, M. LEF1‐mediated MMP13 gene expression is repressed by SIRT1 in human chondrocytes. FASEB J. 31, 3116–3125 (2017). www.fasebj.org